Corporate Governance dan Profitabilitas terhadap Penghindaran Pajak. Bagaimana Pengaruhnya? - Devia Oktaviana; Nur Kholis (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to examine and analyze the effect of corporate governance and profitability on tax avoidance. This study uses tax avoidance as the dependent variable as measured by the Effective Tax Rate (ETR). The variables tested include institutional ownership, independent commissioners, audit committee, audit quality and profitability. This research uses quantitative methods. All companies engaged in the consumer goods sector listed on the IDX (Indonesia Stock Exchange) are the population in this study. In a period of 5 years, namely 2015 to 2019, amounting to 11 companies with a total of 55 observational data, secondary data in this study were on the selected companies then analyzed the company’s annual report. Access to find out the company’s financial report on the website www.idx.co.id and the websites of each company. The sample used in this study using purposive sampling method. The final result of this study indicate that institusional ownership, independent commissioners, audit committee, audit quality and profitability have a significant effect on tax avoidance.